Pengaruh Media Pembelajaran VirtualLab Berbasis PBL Terhadap Keterampilan Berpikir Kritis dan Hasil Belajar Materi Sistem Ekskresi Siswa Kelas VIII SMPN 7 Samarinda: - - Damayanti, Febby; Maasawet, Eslje Theodora; Tindangen, Makrina; Maria, Vandalitas; Rambitan, Magdalena (UNIB Press, 2024)
This study aimed to determine the effect of PBL-based virtual lab learning media on critical thinking skills and science learning outcomes on the excretory system material of class VIII students of SMPN 7 Samarinda. This study was quantitative with a Quasi Experiment type of research with a pretest posttest control group research design. In critical thinking skills, the results of the N-Gain test were obtained, namely 0.53 with a moderate category and the results of the t-test with a significance value of 0.000 <0.05. In learning outcomes, the results of the N-Gain test were obtained by 0.72 with a high category and the results of the t-test with a significance value of 0.000 <0.05. Thus, it is concluded that the use of PBL-based virtual lab learning media has a significant effect on critical thinking skills and learning outcomes on the excretory system material of class VIII students of SMP Negeri 7 Samarinda.